'Details on the Establishment of Doctor Willis, for the Cure of Lunatics' (1796). Issue 3 (September 2017) - Smith, Leonard; Peters, Timothy
The 'mad-doctor' Dr Francis Willis achieved national and international celebrity following his successful treatment of King George III's first major episode of insanity in 1788–9. At the time of his summons to attend the King, Willis was a well-established provincial practitioner and madhouse proprietor. An anonymous French visitor published a description of Willis's Lincolnshire madhouse and his therapeutic practices in 1796. The translated text of the full article provides a unique insight into the work of a key figure in the historical development of psychological medicine. The accompanying Introduction summarizes Francis Willis's career as a mad-doctor and uses salient information from the original text to place him and his madhouse practice within a contemporary context.